Construction of a mathematical model for dust transport process at an industrial site with a perforated protective screen - Biliaiev, Mykola; Berlov, Oleksandr; Biliaieva, Viktoriia; Kirichenko, Pavlo; Kozachyna, Vitalii; Mashykhina, Polina; Savin, Valerii; Semenenko, Pavlo; Usenko, Andrii; Foris, Svitlana (Eastern-European Journal of Enterprise Technologies, 2026)
This work considers the process of dust pollution of the air at an industrial site when using a protective perforated screen. The removal of dust from contaminated land surfaces in areas where there are coal storage facilities leads to intensive air pollution in working areas. This poses a threat to the health of workers. Therefore, for practice, an important solution is to reduce the level of dust pollution of the air at industrial sites. A likely engineering solution to such a task is to use protective screens, in particular, protective screens with perforations. These screens reduce the speed of the oncoming wind flow, which, in turn, reduces the intensity of dust formation. The location of the screens at an industrial site is important. A laboratory experiment was conducted to determine the patterns of air flow velocity distribution behind a protective screen with perforations. The experimental data showed that the screen makes it possible to reduce the wind flow velocity by 5–6 times over an extension of the order of 2H from the screen (H is the height of the screen). The air flow velocity increases intensively behind the screen in the area 2H–4H. These results make it possible to determine the rational location of the screen relative to the dust formation area. For theoretical assessment of the effectiveness of these screens, a numerical model was built based on the fundamental equations of continuum mechanics. The modeling equations include the dust mass transfer equation and the potential motion equation. Using the constructed numerical model, a computational experiment was conducted, which confirmed the effectiveness of using perforated protective screens: the area of dust air pollution in height decreased almost 3 times. The cost of computer time for conducting a computational experiment is 2 seconds. This makes it possible, when carrying out design work, to perform a series of calculations in a short period of time